2002
DOI: 10.1193/1.1509762
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and Inelastic Seismic Response of Buildings with Damping Systems

Abstract: The effect of damping on the response of elastic and inelastic single-degree-of-freedom systems was studied by nonlinear response-history analysis using earthquake histories that matched on average a 2000 NEHRP spectrum on a stiff soil site for a region of high seismic risk. New displacement reduction factors for levels of damping greater than 5% of critical are presented. New equations to relate inelastic and elastic displacements in the short-period range, for levels of damping greater than 5% of critical, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 8 publications
1
77
0
7
Order By: Relevance
“…al. [15] studied inelastic SDOF systems for a wide range of periods of vibration and showed that added damping has no significant effect on the relation between peak elastic and peak inelastic displacements and also, confirmed the technical basis of FEMA 450 [16] to allow a 25% reduction in the minimum design base shear of damped buildings. Pavlou and Constantinou [17] showed that inelastic steel MRFs with passive dampers designed to achieve similar drifts with conventional MRFs experience lower total floor accelerations than conventional MRFs.…”
Section: Introductionmentioning
confidence: 86%
“…al. [15] studied inelastic SDOF systems for a wide range of periods of vibration and showed that added damping has no significant effect on the relation between peak elastic and peak inelastic displacements and also, confirmed the technical basis of FEMA 450 [16] to allow a 25% reduction in the minimum design base shear of damped buildings. Pavlou and Constantinou [17] showed that inelastic steel MRFs with passive dampers designed to achieve similar drifts with conventional MRFs experience lower total floor accelerations than conventional MRFs.…”
Section: Introductionmentioning
confidence: 86%
“…those associated with the maximum displacement, maximum velocity and maximum acceleration. The effectiveness of the ASCE 7-10 procedure has been extensively evaluated with seismic simulations on steel MRFs with viscous dampers under the design basis and maximum considered earthquake (DBE and MCE, respectively) intensities in [14,15]. Guo and Christopoulos [16] proposed an alternative design procedure for multiple target performance objectives utilizing a graphic tool to estimate peak response parameters of yielding structures with passive dampers either by nonlinear response history analyses or by an equivalent linearization procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized approach neviskozno i frekventno zavisno prigušenje). Generalizovani pristup u analizi prigušenja sistema kroz viskozno i neviskozno prigušenje prikazan je u studiji [2], dok su u [47] razmatrani faktori redukcije pomeranja i ukupne smičuće sile u funkciji prigušenja.…”
Section: Earthquake Engineering Research Institute (Eeri) Midamericaunclassified
“…− nelinearna statička analiza (NSA -Nonlinear Static Analysis); − nelinearna dinamička analiza (NDA -Nonlinear to the analysis of the system's damping through viscous and non-viscous damping is shown in the case [2], while [47] considers the factors of reduction in displacement and total shear force as a function of damping. In [49] various aspects of seismic actions are considered in relation to the "standard" aspects of analysis of behavioural of structures exposed to seismic actions.…”
Section: Opšta Sistematizacija Seizmičkih Analiza I Generalni Tretmanmentioning
confidence: 99%